Do we understand the pathophysiology of GERD after sleeve gastrectomy? - Felińska, Eleni Amelia; Billeter, Adrian; Nickel, Felix; Contin, Pietro; Berlth, Felix; Chand, Bipan; Grimminger, Peter; Mikami, Dean; Schoppmann, Sebastian F.; Müller, Beat P. (Annals of the New York Academy of Sciences, 2020)
Gastroesophageal reflux disease (GERD) is a prevalent problem among obese individuals. For many of these patients, bariatric surgery effectively improves GERD, but it can also worsen or even cause a new onset of GERD.